Reframing Literacy in Islamic Education: Embedding Numeracy and Socio-Cultural Literacy through Project-Based Learning Model - Bagus Cahyanto; Khoiriyah; Titis Angga Rini; Abdul Ghafar Don; Choirotul Sakdiah (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
This paper explores the transformation of learning practices in Islamic elementary schools, particularly the development of integrated literacy encompassing numeracy literacy and sociocultural literacy. The study offers both theoretical and practical contributions to the development of integrated literacy within a curriculum grounded in Islamic values, while simultaneously presenting a pedagogical innovation. A qualitative case study approach was employed, involving interviews with several key informants, observations, and document analysis. The data were analyzed using the interactive model proposed by Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing/verification. The findings reveal that, in the planning stage, teachers: (a) analyze the Learning Outcomes, (b) formulate learning objectives, (c) assess student characteristics, (d) analyze and internalize literacy competencies, and (e) prepare instructional materials. In the implementation stage, teachers ap ABSTRAK Tulisan ini mengekplorasi transformasi pembelajaran di sekolah dasar Islam khususnya untuk mengembangkan literasi terintegrasi yaitu literasi numerasi dan literasi sosial budaya. Penelitian ini memberikan kontribusi teoritis dan praktis pada pembelajaran literasi terintegrasi dalam kurikulum berbasis nilai-nilai Islam sekaligus menawarkan sebuah inovasi pedagogis. Penelitian ini menggunakan pendekatan studi kasus kualitatif dengan melibatkan beberapa informan kunci untuk wawancara, observasi, dan studi dokumentasi. Peneliti menggunakan analisis data interaktif menurut Miles, Huberman, dan Saldana yang meliputi kondensasi data, penyajian data, dan penarikan kesimpulan/verifikasi. Hasil penelitian menunjukkan bahwa dalam perencanaan pembelajaran, guru melakukan (a) analisis Capaian Pembelajaran, (b) menyusun tujuan pembelajaran, (c) menganalisis karakteristik siswa, (d) menganalisis dan menginternalisasi kompetensi literasi, dan (e) menyusun perangkat pembelajaran. Sementara itu dalam pelaksanaan pembelajaran,